Assessing Suitability of Technosols of Varying Granulometry for Ecological Restoration using Native Atriplex lampa and Parkinsonia praecox in the Monte Desert, Argentina - Gonzalez, Florencia del Mar; Fernando Miguel Farinaccio; Pérez, Daniel Roberto; Montero, Carla; Oneto, Maria Elena (Annals of Arid Zone, 2025)
Desertification is the process of land degradation in arid, semi-arid, and dry sub-humid areas, which threatens the sustainability worldwide. Sustainable and innovative management strategies for restoring these degraded lands are essential to combat desertification. Use of industrial products, which creates technosols—an artificial substrates that mimic a conducive environment for plant growth, is one of the promising approaches for controlling desertification. In the present investigation, the sand residues of varying granulometry discarded during shale gas and oil processing as potential components of technosols were evaluated for seedling emergence of Atriplex lampa and Parkinsonia praecox, two native shrubs of Monte Desert of Argentina. The experiment was conducted with coarse and fine sand granulometry substrate and under controlled photoperiod and temperature conditions. Seedling emergence of both species was significantly influenced by granulometry of technosols. A. lampa had shown the highest emergence ( 60%, SE = 7.54), while P. praecox averaged 21% (SE = 2.86). The highest emergence rates for the two species were found in coarse sand granulometry (T0), 50% CG / 50% FG (T2), and 25% CG / 75% FG (T3) ( 49%, SE = 10.20). These results signify the importance granulometry of technosols for seedling establishment for restoration of degraded arid lands